2013
DOI: 10.1371/journal.pone.0081915
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Helminth Diagnostic Test Performance on Estimation of Risk Factors and Outcomes in HIV-Positive Adults

Abstract: BackgroundTraditional methods using microscopy for the detection of helminth infections have limited sensitivity. Polymerase chain reaction (PCR) assays enhance detection of helminths, particularly low burden infections. However, differences in test performance may modify the ability to detect associations between helminth infection, risk factors, and sequelae. We compared these associations using microscopy and PCR.MethodsThis cross-sectional study was nested within a randomized clinical trial conducted at 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
1
26
0
1
Order By: Relevance
“…However, a few prevalence surveys have been carried out with PCR. In a recent study in Kenya on human immunodeficiency virus-infected subjects, RT-PCR (sensitivity, 83.3%) was able to detect more S. stercoralis infections than the combination of wet preparation, the Kato-Katz technique, and FECT (sensitivity, 16.7%) [29]: also, none of the latter methods is adequate for S. stercoralis larva detection. In Bangladesh and in Tanzania, a lower sensitivity of PCR methods than of reference faecal methods was reported for the detection of low-intensity infections [30,31].…”
Section: Prevalence Studiesmentioning
confidence: 93%
“…However, a few prevalence surveys have been carried out with PCR. In a recent study in Kenya on human immunodeficiency virus-infected subjects, RT-PCR (sensitivity, 83.3%) was able to detect more S. stercoralis infections than the combination of wet preparation, the Kato-Katz technique, and FECT (sensitivity, 16.7%) [29]: also, none of the latter methods is adequate for S. stercoralis larva detection. In Bangladesh and in Tanzania, a lower sensitivity of PCR methods than of reference faecal methods was reported for the detection of low-intensity infections [30,31].…”
Section: Prevalence Studiesmentioning
confidence: 93%
“…Multiplex DNA-based techniques can and are being used in epidemiological studies and for the monitoring of integrated control programmes (Basuni et al 2012;Arndt et al 2013;Wiria et al 2013a, b).…”
Section: F U T U R E D I R E C T I O N Smentioning
confidence: 99%
“…, b; Verweij et al 2007b; Polley et al 2011) Nematodes A. lumbricoides ITS-1 (Pecson BM et al 2006; Wiria et al 2010; Basuni et al 2011; Hamid et al 2011; Arndt et al 2013; Mejia et al 2013; Wiria et al 2013) Hookworm ITS (Verweij et al 2007a; Basuni et al 2011; Hamid et al 2011; Jonker et al 2012; Arndt et al 2013; Mejia et al 2013; Schar et al 2013; Wiria et al 2013) S. stercoralis SSU rDNA (ten Hove et al 2009; Basuni et al 2011; Kramme et al 2011; Mejia et al 2013; Schar et al 2013; Sultana et al 2013) T. trichiura SSU rDNA, ITS-1 (Liu et al 2013; Mejia et al 2013) Trematodes C. sinensis ITS-1,ITS-2, NAD-2 (Kim et al 2009; Cai XQ et al 2012; Sanpool O et al 2012) O. viverrini O. viverrini specific repetitive DNA fragment, NAD-Suksumek et al 2008; Intapan et al 2009; Sanpool O et al 2012) Paragonimus ITS-2 (Tantrawatpan et al 2013) SchistosomaSSU rDNA, ITS-2,NADH-1, Cox1, S. mansoni tandem repeat(Gomes et al 2006;Obeng et al 2008;ten Hove et al 2008;Kjetland et al 2009;Wichmann et al 2009;Clerinx et al 2011;Cnops et al 2012;Arndt et al 2013; Aryeetey YA et al 2013; Downs JA et al 2013; Wichmann et al2013) CestodesT. solium Tsol9 repeat sequence, ITS-1(Yera et al 2011;Praet et al 2013) …”
mentioning
confidence: 99%
“…The ability of PCR to specifically amplify minute amounts of pathogen DNA in low intensity infection has revolutionized the diagnosis of many infectious diseases including soil transmitted helminth infection (Nath et al 2013;Arndt et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence rate of 70.0% T. trichiura and 10.7% T. vulpis were observed in a rural community in northwestern Thailand using molecular technique (Areekul et al 2010). Studies conducted across the world revealed the significance of molecular diagnosis of SoilTransmitted Helminths over microscopy methods (Basuni et al 2011;Arndt et al 2013).…”
Section: Discussionmentioning
confidence: 99%